Seasonal Variability and Pathogenicity of Kiwifruit Bacterial Canker Pathogens in Sichuan Province, China - Chengyong He; Zihong Xu; Lingli Wang; Yarui Li; Jing Li; Haiyan Song; Dong Chen; Guoliang Jiang; Meiyan Tu (Pathogens)
Kiwifruit canker disease, caused by different bacterial pathogens, was observed in Sichuan Province, China. Specifically, in the winter and spring seasons, Pseudomonas syringae pv. actinidiae (Psa) was identified as the primary pathogen, causing reddish-brown exudates, branch dieback, and phloem decay. In contrast, during the summer months, Pectobacterium carotovorum subsp. actinidiae (Pca) emerged as the primary causal agent of kiwifruit canker, exhibiting similar symptoms to those caused by Psa, such as exudates from leaf scars and lenticels, xylem necrosis, and branch desiccation. From 55 symptomatic samples, 34 bacterial isolates were obtained, with 28 identified as Psa and 6 as Pca. Pathogenicity tests revealed significant variation in virulence, with Psa isolate G5 and Pca isolate M5 showing the highest pathogenicity on leaves and branches, respectively. Both pathogens caused characteristic necrosis and lesion expansion, fulfilling Koch’s postulates. Phylogenetic analyses confirmed the distinct evolutionary relationships of Psa and Pca isolates. These findings highlight the seasonal variability of kiwifruit canker pathogens and emphasize the need for targeted disease management strategies.